Enhancing Patient Outcomes through Collaboration: The Importance of Teamwork between Nursing, Radiography, Medical Devices, Anesthesia, Clinical Pharmacy, Nutrition and Medical Secretaries - Anfal Homud Saweed Alharbi; Anwar Awad Alanazi; Salha Mohammed Al-Thrwy; Aisha Ahmed Ibrahim Altherwi; Fahad Othman Al-Salloom; Atif Lafi Eid Alrashdi; Ibrahim Mohamed Ahmed Modarbesh; Nouf Ahmed Mohammed Al-Qabi; Maha Ibrahim Sultan; Aliya Abdullah Al-Batyain; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
However, while an integral component at a macro level, collaboration and teamwork are critical in all healthcare settings to improve patient outcomes. Poor team dynamics are associated with negative patient outcomes such as decreased patient satisfaction and increased complications revealing the importance of open and honest processes and team dynamics within surgical teams. Moreover, besides increasing healthcare personal satisfaction in a job, an appropriate scenery of teamwork also has a direct impact on a patient treatment quality. These types of algorithm-driven tactics are new pedagogical tactics that can be leveraged to build upon collaborative learning and refine team interactions and interactions, and ultimately prepares doctors for the rigors of how teaming is done in practice. Also, cultivating a psychological safety climate within the teams promotes open communication and accountability, conducive to improved patient care outcomes. Thus, when integrated, These findings underscore the significance of collaboration in delivering patient-centered and high-standard care. [1].